Ingestion of taxifolin-rich foods affects brain activity, mental fatigue, and the whole blood transcriptome in healthy young adults: a randomized, double-blind, placebo-controlled, crossover study. Issue 8 (22nd March 2023) - Shinozaki, Fumika; Kamei, Asuka; Shimada, Kousuke; Matsuura, Hiroshi; Shibata, Takeo; Ikeuchi, Mayumi; Yasuda, Kayo; Oroguchi, Takashige; Kishimoto, Noriaki; Takashimizu, Shinji; Nishizaki, Yasuhiro; Abe, Keiko
Abstract : Taxifolin, a polyphenol, is a strong antioxidant and is believed to exhibit various functions. This study is the first that showed the possibility of taxifolin to affect brain activity, mental stress and transcriptome in healthy young adults. Abstract : The antioxidant properties of polyphenols, which are found in most plants, have been shown to be useful for maintaining health, including enhancing brain function and alleviating stress. We aimed to investigate the effect of a single intake of taxifolin-containing foods on cognitive task performance and whole blood gene expression in healthy young adults. This study was a randomized, placebo-controlled, double-blind, crossover trial in which healthy young adults were administered a single dose of either a placebo or food containing taxifolin. Cognitive tests (serial 3s, serial 7s, and rapid visual information processing) to examine brain activity and visual analog scale questionnaires to analyze mental fatigue were applied. The set of tests was repeated four times. The findings showed that taxifolin intake improved calculation abilities and reduced mental fatigue. An analysis of whole blood gene expression before and after the test revealed that the expression of foreign substance removal-related genes increased following the ingestion of taxifolin and that most differentially expressed genes were enriched in granulocytes. Taxifolin intake was shown to affect the brain activity of healthy young adults and demonstrated an antifatigue effect, thereby reducing subjective fatigue. A single intake of taxifolin may enhance the removal of foreign substances by strengthening the innate immune system and suppressing the occurrence of injury.